2021
DOI: 10.4143/crt.2020.1191
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Effects of Chemotherapy for Colorectal Cancer: A Systematic Review and a Meta-Analysis of 11 Studies

Abstract: Chemotherapy-related cognitive impairment (CRCI) is a controversial concept not much explored on colorectal cancer patients. Materials and Methods We identified eleven prospective studies: eight studies on 696 colorectal cancer patients who received chemotherapy and three studies on 346 rectal cancer patients who received neoadjuvant chemoradiotherapy. Standardized mean differences (SMDs) of neuropsychological test results and the cognitive quality-of-life scale were calculated using random effect models. A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…a h e a d o f p r i n t regression from our previous systematic review and meta-analysis on cognitive decline after chemotherapy in colorectal cancer patients suggested that older colorectal cancer patients are more likely to suffer from cognitive impairment after receiving chemotherapy, [12] further supporting the hypothesis. However, the studies that we previously reviewed consisted of studies utilizing relatively small and selected populations (N<500).…”
Section: E P U Bmentioning
confidence: 67%
See 1 more Smart Citation
“…a h e a d o f p r i n t regression from our previous systematic review and meta-analysis on cognitive decline after chemotherapy in colorectal cancer patients suggested that older colorectal cancer patients are more likely to suffer from cognitive impairment after receiving chemotherapy, [12] further supporting the hypothesis. However, the studies that we previously reviewed consisted of studies utilizing relatively small and selected populations (N<500).…”
Section: E P U Bmentioning
confidence: 67%
“…It has been hypothesized that older patients with cancer are vulnerable to cognitive impairment after chemotherapy [ 9 ], as their cognitive reserve—the capacity of the brain to sustain external and internal neuropathological burdens [ 10 ]—is diminished [ 11 ]. A meta-regression from our previous systematic review and meta-analysis on cognitive decline after chemotherapy in colorectal cancer patients suggested that older colorectal cancer patients are more likely to suffer from cognitive impairment after receiving chemotherapy [ 12 ], further supporting this hypothesis. However, the studies that we previously reviewed utilized relatively small and selected populations (n<500).…”
Section: Introductionmentioning
confidence: 84%
“…It has been hypothesized that older patients with cancer are vulnerable to cognitive impairment after chemotherapy, [9] as their cognitive reserve, the capacity of the brain that helps it sustain the external and internal neuropathological burden, [10] are diminished. [11] A meta-regression from our previous systematic review and meta-analysis on cognitive decline after chemotherapy in colorectal cancer patients suggested that older colorectal cancer patients are more likely to suffer from cognitive impairments after receiving chemotherapy, [12] further supporting the hypothesis. However, previous studies that our group reviewed consisted of studies utilizing relatively small and selected population (N<500), so epidemiologic evidence from nationwide representative population with large sample is warranted.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies on "chemo-brain" in colorectal cancer patients did not suggest consistent direction of evidence4, 5. Our previous meta-analysis of previous studies showed that older patients are more likely to experience cognitive impairments after chemotherapy [12], but studies our groups reviewed had limited numbers of participants within each study, limiting the statistical power. Additionally, the effects of each chemotherapy agents were not described separately in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impaired cognition was related to anxiety, depression, fatigue and poorer QOL, which suggested that these negative concomitant symptoms might be associated with cancer-related distress or negative appraisal and decreased tolerance or resilience to manage cancer-related pain and chemotherapy-related side-effects ( 11 13 ). A meta-analysis study also found that older CRC patients were more vulnerable to cognitive impairment after chemotherapy, and preventive measures and rehabilitation programs could reduce the risk of developing chemotherapy-induced cognitive impairment ( 14 ). A prospective, longitudinal, controlled study showed that 36%-52% CRC patients had cognitive impairment including working memory, attention, verbal memory and processing speed ( 15 ).…”
Section: Introductionmentioning
confidence: 99%